Building Infectious Disease Research Programs to Promote Security and Enhance Collaborations with Countries of the Former Soviet Union - Bartholomew, James C.; Pearson, Andrew D.; Stenseth, Nils Chr.; LeDuc, James W.; Hirschberg, David L.; Colwell, Rita R. (Frontiers in Public Health, 2015)
Addressing the threat of infectious diseases, whether natural, the results of a laboratory accident, or a deliberate act of bioterrorism, requires no corner of the world be ignored. The mobility of infectious agents and their rapid adaptability, whether to climate change or socioeconomic drivers or both, demand the science employed to understand these processes be advanced and tailored to a country or a region, but with a global vision. In many parts of the world, largely because of economic struggles, scientific capacity has not kept pace with the need to accomplish this goal and has left these regions and hence the world vulnerable to infectious disease outbreaks. To build scientific capability in a developing region requires cooperation and participation of experienced international scientists who understand the issues and are committed to educate the next generations of young investigators in the region. These efforts need to be coupled with the understanding and resolve of local governments and international agencies to promote an aggressive science agenda. International collaborative scientific investigation of infectious diseases not only adds significantly to scientific knowledge, but it promotes health security, international trust, and long-term economic benefit to the region involved. This premise is based on the observation that the most powerful human inspiration is that which brings peoples together to work on and solve important global challenges. The republics of the former Soviet Union provide a valuable case study for the need to rebuild scientific capacity as they are located at the crossroads where many of the world’s great epidemics began. The scientific infrastructure and disease surveillance capabilities of the region suffered significant decline after the breakup of the Soviet Union. The U.S. Cooperative Threat Reduction (CTR) Program, a part of the U.S. Department of Defense, together with partner countries, have worked diligently to improve the capabilities in this region to guard against the potential future risk from especially dangerous pathogens. The dissolution of the Soviet Union left behind many scientists still working to study pathogens using antiquated protocols in unsafe laboratories. To address this situation, the CTR program began improving laboratory infrastructure, establishing biosafety and biosecurity programs, and training scientists in modern techniques, with emphasis on biosurveillance and safe containment of especially dangerous pathogens. In the Republic of Georgia, this effort culminated in the construction of a modern containment laboratory, the Richard G. Lugar Center for Public Health Research in Tbilisi to house both isolated especially dangerous pathogens as well as the research to be conducted on these agents. The need now is to utilize and sustain the investment made by CTR by establishing strong public and animal health science programs in these facilities tailored to the needs of the region and the goals for which this investment was made. A similar effort is ongoing in other former Soviet Republics. Here, we provide the analysis and recommendations of an international panel of expert scientists appointed by the Cooperative Biological Engagement Program of the Defense Threat Reduction Agency to provide advice to the stakeholders on the scientific path for the future. The emphasis is on an implementation strategy for decision makers and scientists to consider providing a sustainable biological science program in support of the One Health initiative. Opportunities, potential barriers, and lessons learned while meeting the needs of the Republic of Georgia and the Caucasus region are discussed. It is hoped that this effort will serve as a model for similar scientific needs in not only the former Soviet Union republics but also other regions challenged by infectious diseases where the CTR program operates.